2011
DOI: 10.1021/bi101724h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of 6′-N-5-Hexynoate Kanamycin A and RNA 1x1 Internal Loops Containing CA Mismatches

Abstract: In our previous study to identify the RNA internal loops that bind an aminoglycoside derivative, we determined that 6′-N-5-hexynoate kanamycin A prefers to bind 1×1 nucleotide internal loops containing C•A mismatches. In this present study, the molecular recognition between a variety of RNAs that are mutated around the C•A loop and the ligand was investigated. Studies show that both loop nucleotides and loop closing pairs affect binding affinity. Most interestingly, it was shown that there is a correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…For example, A/C mismatches are isosteric with G•U wobble pairs, although their stability is influenced by nearest-neighbor identity (41). In pri-mir-16-1, the A/C mismatch is neither reactive to the SHAPE reagent or RNase A cleavage (Table 1); nor is it predicted to be highly disordered by MC-Fold, which is consistent with the structure of an A/C mismatch from the large ribosomal subunit found in an identical sequence context (42).…”
Section: Resultsmentioning
confidence: 99%
“…For example, A/C mismatches are isosteric with G•U wobble pairs, although their stability is influenced by nearest-neighbor identity (41). In pri-mir-16-1, the A/C mismatch is neither reactive to the SHAPE reagent or RNase A cleavage (Table 1); nor is it predicted to be highly disordered by MC-Fold, which is consistent with the structure of an A/C mismatch from the large ribosomal subunit found in an identical sequence context (42).…”
Section: Resultsmentioning
confidence: 99%
“…Dissociation constants were determined using an in-solution, fluorescence-based assay 20,21,4851,54,55,58 . A selected RNA or RNA mixture was folded as described above.…”
Section: Methodsmentioning
confidence: 99%
“…X-ray crystallographic and NMR structure studies of ribosomes and rRNA fragments revealed that various aminoglycoside antibiotics inhibit translation by direct binding to architectural elements within the 16S rRNA and demonstrated that RNA can be specifically targeted by small molecules. The array of RNA motifs that can be specifically bound by small molecules and the chemotypes of those small molecules has been expanded through small molecule library-RNA motif library screens 1,41 . However, with few exceptions 30 , rational design of chemical inhibitors targeting specific RNA motifs has been less productive due in part to lack of reliable in silico and experimental tools for structure-based drug design.…”
Section: Resultsmentioning
confidence: 99%